Autonomic correlates of Yo-Yo performance in soccer referees Correlatos autonômicos do desempenho no Yo-Yo em árbitros de futebol - Daniel A. Boullosa; Fábio Yuzo Nakamura; Luiz Augusto Perandini; Anthony Scott Leicht (Universidade Estadual Paulista (UNESP), 2012)
We tested the hypothesis that: basal cardiac autonomic modulation (i.e. heart rate variability, HRV) was associated with the parasympathetic withdrawal during, and overall Yo-Yo IR1 performance; and therefore HRV could be used as a simple tool for specific fitness assessment. Nine sub-elite soccer referees performed the Yo-Yo IR1 until exhaustion with simultaneous recording of heart rate with the autonomic response during exercise calculated as the area under the curve (AUC). In the same week but with at least 48 hrs between days, a night-time HR recording was obtained from participants for determination of basal HRV. Correlation analysis demonstrated strong (r>0.83) relationships among Yo-Yo IR1 performance, AUC and basal HRV. These results indicate that both nocturnal HRV and AUC can be utilised as simple and valid monitoring tools of soccer referees' fitness. Nós testamos a hipótese de: que a modulação autonômica cardíaca (i.e. variabilidade da freqüência cardíaca, VFC) está associada com a retirada parassimpática durante a execução do Yo-Yo IR1; e que, portanto, a VFC poderia ser usada como uma ferramenta simples para a avaliação do desempenho físico específico. Nove árbitros sub-elite de futebol executaram o Yo-Yo IR1 até a exaustão com registro simultâneo da freqüência cardíaca e VFC para o cálculo da área sob a curva (ASC). Na mesma semana, mas com mínimo de 48 horas entre dias, obteve-se um registro noturno da FC dos participantes para a determinação da VFC basal. As análises de correlação demonstraram elevados coeficientes (r>0,83) entre o desempenho no Yo-Yo IR1, a ASC e a VFC basal. Estes resultados indicam que a VFC noturna e a ASC podem ser empregadas como ferramentas simples e válidas para o monitoramento do desempenho de árbitros de futebol.